The prevalence of gram negative bacteria in bovine mastitis among dairy herds in Nigeria (2009)
The dairy industry in Nigeria has not been well developed due to several factors of which bacterial mastitis play a prominent role. The current study was to determine the prevalence of gram negative bacteria in clinical cases of bovine mastitis from different ecological zones of Nigeria. Bacteriological examination of milk samples from 200 clinically infected cows was performed through characterization of replicate samples. A total of 205 isolates belonging to three bacteriological genera were identified. Escherichia coli, Klebsiella pneumoniae and Pseudomonas aeruginosa had prevalence of 53.66%, 32.68% and 13.66% respectively. The isolates were widely distributed across the southern, middle belt and northern Nigeria with prevalence of 38.05%, 32.68% and 29.68% respectively. There was significant difference (p<0.05) in the prevalence of different isolates from across the regions. The result is of economic and public health importance due to cross contamination of milk from cows in the same herd and as a result of traditional unhygienic hand milking method employed by the herdsmen. Consumption of such unpasteurized milk is also a frequent occurrence among the rural dwellers; this could lead to milk borne zoonoses, while the reduction in milk production due to these infections caused economic losses. Control and prevention of these infections through hygienic milking operation, herd health and husbandry education of the traditional herdsmen will help to improve productivity of the dairy industry in Nigeria.